Broadway or West End: influences of Anglophone musicals in production of musicals in (and from) Brazil (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper was intended to raise a question about the nomenclature given to a style of Musical Theatre, which is commonly designated in Brazil as a “Broadway musical”, in a kind of categorization of a musical style rather than a designation of the origins of the show. The proposal presented in this paper is to name these spectacles as “Anglophone musicals” – since many of these musicals imported to Brazil had their origins both in the West End (in London) and on Broadway (in New York) – and present their influences in the growth of this theatrical style in contemporary Brazil, both in the production of these imported musicals performed “in” Brazil as in the production of original musicals “from” Brazil.
Keywords: Broadway; West End; Anglophone Musicals; Influences; Brazilian Musical Theatre